A novel design of water environment monitoring system based on WSN - Ning Jin; Renzhi Ma; Yunfeng Lv; Xizhong Lou; Qingjian Wei (2010 International Conference On Computer Design and Applications, 2010)
The importance of maintaining good water environment highlights the increasing need for advanced technologies. This paper proposes a novel design of water environment monitoring system based on wireless sensor networks (WSN). The system consists of three parts: sensor nodes; sink nodes and data monitoring center. The sensor nodes can be constructed with arbitrary parameter or multi-parameter sensor modules such as PH, dissolved oxygen (DO), conductivity and temperature. The measurement capacity ranges from 0 to 14 on PH value; from 0~20 mg/L on DO; from 0~2 S/cm on conductivity. The sink nodes communicate with the local or remote data monitoring center by RS232 or 3 G/GPRS. The performance shows the system can be effectively applied to some water area such as aquiculture, lake and river for distributed water environment automatic monitoring.